2012
DOI: 10.1021/cb300329r
|View full text |Cite|
|
Sign up to set email alerts
|

Selective Penicillin-Binding Protein Imaging Probes Reveal Substructure in Bacterial Cell Division

Abstract: The peptidoglycan cell wall is a common target for antibiotic therapy but its structure and assembly are only partially understood. Peptidoglycan synthesis requires a suite of penicillin-binding proteins (PBPs), the individual roles of which are difficult to determine because each enzyme is often dispensable for growth perhaps due to functional redundancy. To address this challenge, we sought to generate tools that would enable selective examination of a subset of PBPs. We designed and synthesized fluorescent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
80
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 40 publications
1
80
3
Order By: Relevance
“…6, pseudocolored green). A fluorescent cephalosporin (Ceph C-T) characterized previously specifically labels only PBP1b and PBP3 (DacA) in S. pneumoniae but not other PBPs (47). PBP1b and PBP3 (DacA) localize to the septum of dividing cells or over the surface, respectively, as indicated by Ceph C-T labeling (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…6, pseudocolored green). A fluorescent cephalosporin (Ceph C-T) characterized previously specifically labels only PBP1b and PBP3 (DacA) in S. pneumoniae but not other PBPs (47). PBP1b and PBP3 (DacA) localize to the septum of dividing cells or over the surface, respectively, as indicated by Ceph C-T labeling (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…The latter hypothesis is supported by the results of the resistance studies described herein, in which resistance, although low, mapped to other genes related to cell wall biosynthesis besides pbp3, with concomitant slight increases in sulbactam MICs (Table 4). While the morphological changes in A. baumannii upon exposure to sulbactam described above suggest that pbp3 inhibition does indeed occur, further investigation of the relative contribution of this enzyme inhibition to overall whole-cell killing could potentially be accomplished using more sophisticated microscopic approaches, such as direct detection of target binding in situ with fluorescently labeled derivatives, as described by Kocaoglu and colleagues (46). Alternatively, chemical proteomics, a recently developed platform that allows the identification of all proteins that specifically interact with small molecules of interest (47), may be a useful approach to further define the targets of inhibition for sulbactam.…”
Section: Figmentioning
confidence: 99%
“…Our recent study using superresolution microscopy revealed that PBP2x of S. pneumoniae is directed to a discrete location separate from PBP2b and PBP1a within the septal aperture during the later stages of cell division (12). Selective fluorescent ␤-lactam chemical probes would provide further insight by visualization of the TP activity of PBPs at different stages of bacterial cell division (25,26).…”
mentioning
confidence: 99%
“…More recently, nonradioactive ␤-lactams, such as fluorescent derivatives, have been used to detect PBPs in both gel-based analyses (23,24) and localization studies in live cells (25,26). Previous PBP profiling with ␤-lactams was performed with the laboratory strains R36A and R6 (10,22,27,28).…”
mentioning
confidence: 99%